Perceptions of secondary school teachers on the proposed grade nine exit plan policy: the case of two secondary schools in Johannesburg, Gauteng - Mohammed, Adillah Abdallah (University of the Witwatersrand, Johannesburg, 2022)
The Department of Basic Education (DBE) intends to introduce the General Education Certificate (GEC). The GEC would allow learners to exit the mainstream schooling system at the end of grade nine for vocational training or jobs. The GEC policy aims to reduce the high dropout rates between grades ten and eleven. This study sets out to establish the perceptions of grade nine teachers on the introduction of GEC. The critical theory framework underpinned the study, which questioned how the education system can best offer education to all learners irrespective of their socioeconomic status. This study used a qualitative research approach. The study sample comprised of fourteen participants from two public schools in Johannesburg. Seven participants from each of the two schools. Purposive sampling was utilised to select the participants. Semi-structured interviews were used to collect data. Face-to-face interviews were conducted on an individual basis. The data was analysed utilising thematic analysis. The participants perceive the GEC to be inclusive in nature as it accommodates all leaners with different learning needs and abilities. The GEC is perceived as a path to implementing inclusive education for equitable opportunities for all learners, for a just and less discriminative society. A noted concern was that the learners may use the GEC as an exit ticket from the schooling system. Participants indicated that a mechanism to ensure that all learners leaving the schooling system get absorbed in technical colleges for further training is required. They noted that the learners are too young to decide on their career paths at grade nine. A selection criterion to guide the identification of learners permitted to exit at grade nine, further engagement with key stakeholders, expansion and opening of more skills-based colleges, training, and funding of schools and skills-based colleges were recommended.
A report on a research study presented in partial fulfillment of the requirements for the degree Master of Arts in the field of Social Development, to Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2022.
Keywords: General Education Certificate (GEC); Grade Nine; School Dropout; Secondary school teachers’ perceptions; UCTD; SDG-4: Quality education